Phosphorus deficiency diagnosis in sheep using labeled phosphorus uptake by erythrocytes - Antunes, Dalton Araujo; Louvandini, Helder; Filho, José Cleto da Silva; McManus, Concepta Margaret; Dallago, Bruno Steffano; Machado, Bruno de Oliveira; Mendonça, Dharana Guedes; Correa, Patrícia Spoto (Pesquisa Agropecuaria Brasileira, 2006)
This work had the objective of evaluating the method of 32P uptake by the erythrocytes of young sheep, supplemented with phosphorus and kept at pasture of Andropogon gayanus, as a tool for phosphorus deficiency diagnosis. Twenty lambs, initially weighing 13.88±2.51 kg, were divided in two treatments of ten animals each. In one of them, animals were supplemented with 3 g of phosphorus per animal per day and, in the other, animals did not receive supplementation of phosphorus. Weighing, and blood and faeces collection were carried out in the 8th, 29th, 43rd, 57th e 71st days of the experiment, to evaluate the incorporation of 32P by the erythrocytes, to determine calcium, glucose and phosphorus concentrations in the serum and percentage of P in the faeces. Significant difference for the concentration of Ca was found in the 57th day. For the glucose concentration, the percentage of phosphorus in faeces, and the weight, significant differences between the treatments were not observed. From the 29th to the 71st day, the concentration of phosphorus in the serum was higher, and the incorporation of 32P was lower in the group of animals supplemented with phosphorus. The analysis of 32P incorporation by the erythrocytes is an additional tool to evaluate the status of P, with identification of the subclinic deficiency in lambs.